Role of melatonin in enhancing arbuscular mycorrhizal symbiosis and mitigating cold stress in perennial ryegrass (Lolium perenne L.) - Wei, Hongjian; Wang, Jiajin; Wang, Qi; He, Wenyuan; Liao, Songkai; Huang, Jiahao; Hu, Wentao; Tang, Ming; Chen, Hui (Frontiers in Microbiology, 2023)
Melatonin is a biomolecule that affects plant development and is involved in protecting plants from environmental stress. This investigation aimed to scrutinize the mechanism of melatonin’s impact on arbuscular mycorrhizal (AM) symbiosis and cold tolerance in perennial ryegrass (Lolium perenne L.). The study was conducted in two parts. The initial trial examined two variables, AM inoculation, and cold stress, to investigate the involvement of the AM fungus Rhizophagus irregularis in endogenous melatonin accumulation and the transcriptional levels of its synthesis genes in the root system of perennial ryegrass under cold stress. The subsequent trial was designed as a three-factor analysis, encompassing AM inoculation, cold stress, and melatonin application, to explore the effects of exogenous melatonin application on plant growth, AM symbiosis, antioxidant activity, and protective molecules in perennial ryegrass subjected to cold stress. The results of the study showed that compared to non-mycorrhizal (NM) plants, cold stress promoted an increase in the accumulation of melatonin in the AM-colonized counterparts. Acetylserotonin methyltransferase (ASMT) catalyzed the final enzymatic reaction in melatonin production. Melatonin accumulation was associated with the level of expression of the genes, LpASMT1 and LpASMT3. Treatment with melatonin can improve the colonization of AM fungi in plants. Simultaneous utilization of AM inoculation and melatonin treatment enhanced the growth, antioxidant activity, and phenylalanine ammonia-lyase (PAL) activity, while simultaneously reducing polyphenol oxidase (PPO) activity and altering osmotic regulation in the roots. These effects are expected to aid in the mitigation of cold stress in Lolium perenne. Overall, melatonin treatment would help Lolium perenne to improve growth by promoting AM symbiosis, improving the accumulation of protective molecules, and triggering in antioxidant activity under cold stress.